Synthesis of Biologically Important Angiotensin-II and Angiotensin-IV Peptides by Using 4-(2’,4’-Dimethoxypenyl-Fmoc-Aminomethyl)phenoxy Resin - Selvam, R.; Rohini, K.C.; Arunan, C.; Subashchandran, K.P. (Asian Journal of Chemistry, 2013)
In peptide chemistry, there is the goal to produce pure biologically active peptides with the highest possible efficiency, even its possible by chemical synthesis purity and yield as a major problem. In this work, we focus to overcome above difficulty by novel synthetic approach. Angiotensin an oligopeptide is a hormone and a powerful dipsogen, which exhibits a wide range of biological activities, the 8-amino acid sequence Angiotensin-II and 6-amino acid sequence. Angiotensin-IV were synthesized by using 4-(2',4'-dimethoxyphenyl-Fmoc-aminomethyl) phenoxy resin, the modified Fmoc-chemistry and effective hydroxybenzenetriazole, N,N'-diisopropylcarbodiimide coupling and activation methods was used. The yield and chromatographic purities were compared.